Sputum colour: An indicator of Legionella pneumophila pneumonia - Toshiyuki Sumi; Keito Suzuki; Yuta Koshino; Takumi Ikeda; Yuichi Yamada; Hirofumi Chiba (Respirology Case Reports, 2024)
Key message The sputum colour in patients with severe pneumonia needs to be considered during diagnosis.